2014
DOI: 10.4315/0362-028x.jfp-14-087
|View full text |Cite
|
Sign up to set email alerts
|

Active Monoterpene Ketones Isolated from Rosmarinus officinalis with Fumigant and Contact Action against Tyrophagus putrescentiae (Schrank)

Abstract: The acaricidal activities of an active material derived from Rosmarinus officinalis oil and its relative monoterpene ketones were determined using fumigant and contact toxicity bioassays against Tyrophagus putrescentiae and were compared with that of a commercial acaricide (benzyl benzoate). The active component of R. officinalis oil, isolated by silica gel column chromatography and high-performance liquid chromatography, was identified as camphor, based on various spectroscopic analyses. In the fumigant toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although camphor showed higher toxicity than 1,8-cineole in certain other insects and arthropods such as the armyworm, Pseudaletia unipuncta 56 , and the food mite, Tyrophagus putrescentiae 57 , 1,8-cineole has long been considered as the active insecticidal constituent of rosemary oil against many arthropod species including the cabbage looper 6 56 and stored-product insects 58 because of its high concentration in the oil and higher individual bioactivity. In the present study, however, camphor showed better internal toxicity (via injection) with enhanced penetration, indicating its more significant contribution to overall toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although camphor showed higher toxicity than 1,8-cineole in certain other insects and arthropods such as the armyworm, Pseudaletia unipuncta 56 , and the food mite, Tyrophagus putrescentiae 57 , 1,8-cineole has long been considered as the active insecticidal constituent of rosemary oil against many arthropod species including the cabbage looper 6 56 and stored-product insects 58 because of its high concentration in the oil and higher individual bioactivity. In the present study, however, camphor showed better internal toxicity (via injection) with enhanced penetration, indicating its more significant contribution to overall toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Guazzi et al (2001) collected the volatile oils of rosemary under different microclimate conditions for chromatographic analysis and identified hydrocarbons (59.2%), aldehydes and ketones (24.3%), alcohols (9.1%), as well as other related small molecules (7.3%) as the critical chemical constituents. Usually, the monoterpene hydrocarbons presented in rosemary essential oil include α-pinene, β-pinene, 1,8-cineole, camphor, linalool, borneol, camphene, α-terpineol, myrcene, bornyl acetate, α-terpinene, terpinen-4-ol, limonene, and verbenone (Figure 4), and the bicyclic monoterpenes were the dominant hydrocarbons in rosemary oil (90.38%) (Jeon et al, 2014).…”
Section: Essential Oilsmentioning
confidence: 99%
“…Furthermore, Rosmarinus officinalis L. essential oil (EO) and its constituent compounds were active against this mite, both as a fumigant (LD 50 = 8.24 µg/cm 3 ) and in contact toxicity (LD 50 = 5.49 µg/cm 2 ). The constituent camphor appeared to be successful in combating the pest (fumigant toxicity LD 50 = 2.25 µg/cm 3 , contact toxicity LD 50 = 1.34 µg/cm 2 ) more effectively than benzyl benzoate (LD 50 = 12.56 µg/cm 3 , and 9.03 µg/cm 2 ) [22]. Other constituent substances in rosemary oil are α-pinene, 1,8-cineole and camphene, all exhibiting miticidal activity [23].…”
Section: Economically Important Groups Of Stored-product Pests and Plant-derived Tools With Reported Activity 21 Mites (Acari)mentioning
confidence: 99%